1994
DOI: 10.1002/hlca.19940770135
|View full text |Cite
|
Sign up to set email alerts
|

Radical Reactions in an X‐Irradiated Phosphaalkene: A single‐crystal ESR study

Abstract: (5.VII.93)Single crystals of 1-[2,4,6-tri(wrt -butyl)phenyl]-2-phenylphosphaetbene (PPPE) and of 'D-and "C-enriched PPPE were studied by ESR after X-ray irradiation. Two phosphorus-centered radicals were trapped in the crystals. The first one was characterized by its 3'P, 'H-, and '3C-hyperfine tensors, the second one exhibited coupling with "P only. Comparison of these parameters with those predicted by ub initio calculations on some phosphinyl species indicates that these two radicals probably result, on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…On the other hand, the formation of C-centered radicals attached to a phosphorus atom has been previously described . The evidence is strongly against any significant C−P dπ−pπ bonding in the ground state of these radicals and agrees with spin-density essentially localized on the carbon atom.…”
supporting
confidence: 66%
“…On the other hand, the formation of C-centered radicals attached to a phosphorus atom has been previously described . The evidence is strongly against any significant C−P dπ−pπ bonding in the ground state of these radicals and agrees with spin-density essentially localized on the carbon atom.…”
supporting
confidence: 66%
“…We have already shown, , that the most stable geometry of a HP−CR 3 phosphinyl radical corresponds to the staggered configuration (HPCR dihedral angle = 180°). The salient feature of the spectra obtained with the phosphinyl radical R2 trapped in the crystal of 2 is that each “site” detected at room temperature seems to generate only two “configurational sites” at 77 K. This is in contrast with the situation observed with a crystal of D-1 where the P−D bond of the phosphinyl radical is blocked, at 77 K, with the same probability along the three orientations staggering the barrelene C 9 −C bonds.…”
Section: Discussionmentioning
confidence: 92%
“…In the case of diph~sphene~,~ it was shown that the P=P moiety rapidly reacts with radicals to produce phosphinyl radicals (RzP) and more recently we could demonstrate, from solid-state EPR studies, that this mechanism occurs as well for the P 4 fragment. 5 In the present paper, we report another radical process involving the phosphaalkene group and show that, under radiolysis, the -P=C< bond can give rise to a phosphoniumyl radical cation (R3P+').…”
Section: Introductionmentioning
confidence: 96%